2017
DOI: 10.1016/j.actbio.2017.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced human bone marrow mesenchymal stromal cell adhesion on scaffolds promotes cell survival and bone formation

Abstract: Around 10% of skeletal fractures do not heal correctly causing nonunion. An approach involving mesenchymal stromal cells (MSC) associated with biomaterials emerges as an innovative strategy for bone repair. The diversity of scaffolds is a source of heterogeneity for bone formation efficiency. In order to better determine the characteristics of a powerful scaffold it is crucial to understand their relationship with cells after graft. Our results highlight that a biomaterial architecture similar to cancellous bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 53 publications
1
52
0
5
Order By: Relevance
“…This density does not seem to be a limiting factor. Indeed, the best results in several similar studies were obtained on granules with densities ranging from 90,000 to 125,000 cells per milligram (Léotot et al, ; Mankani, Kuznetsov, Fowler, Kingman, & Robey, ; Mebarki et al, ). It should be noted, however, that the presence or absence of vessels was not assessed in these studies.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This density does not seem to be a limiting factor. Indeed, the best results in several similar studies were obtained on granules with densities ranging from 90,000 to 125,000 cells per milligram (Léotot et al, ; Mankani, Kuznetsov, Fowler, Kingman, & Robey, ; Mebarki et al, ). It should be noted, however, that the presence or absence of vessels was not assessed in these studies.…”
Section: Discussionmentioning
confidence: 97%
“…We did not observe a direct contribution of transplanted WJMSC‐OBs to bone formation; no human‐osteopontin‐positive cells were detected in the implant. To the best of our knowledge, the studies that found a direct contribution of implanted cells in bone regeneration were always performed with MSCs and not OBs derived from MSCs (Mebarki et al, ). Differentiated cells might not be able to integrate into the neotissues.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, enhanced MSC adhesion was recently demonstrated to promote cell survival and bone formation (Mebarki et al, ). Because the 152RM peptide greatly enhanced MSCs adhesion and increased the ratio and quantity of MSCs retained in the SCR procedure, future in vivo studies might demonstrate an enhanced bone formation capability of the 152RM peptide group.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on animal models shown that differences in bone formation depend on the biomaterial's capacity to select and guide MSCs behavior. In bone tissue engineering, scaffolds provide a mechanical and biochemical microenvironment for MSCs [6]. The MTT assay also enables the assessment of viability of cells in contact with studied biomaterials [16].…”
Section: Mtt Testmentioning
confidence: 99%